Stress and job satisfaction among school teachers in Malaysia: The association with the psychosocial working environment and organizational justice / Harish Raj Narandaran - Harish Raj , Narandaran (2018)
Teachers have been observed to be experiencing an increased incidence of work-related stress in Malaysia. Specific psychosocial working environment (PWE) characteristics and fairness at work in the teaching profession are such pertinent factors that evolve into negative sequelae of work such as stress and job dissatisfaction. Growing disillusionment in the teaching profession has gradually manifested into various somatic and psychological symptoms. Issues pertaining to psychological wellbeing have been found to influence productivity. Schools have reported teachers’ dissatisfaction with their jobs, and stress-induced illnesses often affect work performance, job commitment and dedication. Teachers work closely with the nation’s youth, thus are imperative in passing positivity. PWE and organizational justice (OJ) models are widely used workstress models and have been found to be consistent in predicting physical, mental and psychological health outcomes in varying occupational groups, including teachers. This study was conducted in three phases. Phase I included the psychometric assessment of the translated Malay language version of the Organizational Justice Scale Questionnaire (OJSQ) and Job Satisfaction Survey (JSS) questionnaire. It consisted of assessments in terms of internal consistency, test-retest reliability and Exploratory Factor Analysis of the translated instruments. Phase II was the assessment of PWE and OJ incidence, risk factors and distribution in relation to stress and job satisfaction amongst school teachers in Selangor. Participants were recruited in a cross-sectional manner via multi-stage random sampling of teachers serving in regular public secondary and vernacular schools. Analyses included weightage imputations, descriptive statistics, complex- iv sample and multivariable fixed-effects analysis. Phase III consisted of an objective subsample analysis to determine the correlation between salivary cortisol and secretory IgA with stress. Phase I: The Malay language version of the OJSQ and JSS demonstrated good psychometric properties and a reliable instrument among Malay speaking teachers. Phase II: Approximately 38.6% of teachers reported high job strain. Although higher job demand (JD) and lower job control (JC), social support (SS) and OJ were associated with higher stress scores, no statistical significance was found (p>0.05). Higher JC (p <0.05, 95% CI 145.4-151.94), SS (p <0.001, 95% CI 151.6, 159.4) and higher OJ scores (PJ: p <0.05, 95% CI 145.3, 152.4; IJ: p <0.05, 95% CI 147, 154.5; DJ: p <0.05, 95% CI 148.1, 156.1) was however associated with higher levels of job satisfaction. After correcting for socio-demographic and working characteristics, higher JC (β - 6.16, 95% CI 1.82, 10.5), SS (β - 13.22, 95% CI 8.45, 17.9.5), PJ (β – 2.21, 95% CI 1.79, 4.21), IJ (β - 3.85, 95% CI 2.32, 7.38) and DJ (β - 10.14, 95% CI 6.5, 13.74) were significantly associated with higher job satisfaction. Phase III: No correlation was reported between salivary stress biomarkers and stress scores. Higher levels of JC, SS and OJ factors correlated with higher levels of job satisfaction and although no statistical significance was found, there was however, a correlation between PWE and OJ factors with stress scores. These findings should be proposed the Ministry of Education’s Occupational Safety and Health committee to set precedence in improving teachers’ working environment and conditions via continuity of research and intervention modules